Rangeland Development and Management in West Rajasthan - Ahuja, L D; Mann, H S (Annals of Arid Zone, 2016)
Range and Pasture development in the arid zone of Rajasthan offers a good prospect, but it involves development and conservation of soil and water resources, and selection of the more productive, palatable and drought resistant plant species to provide the required food there. The methodology of rangeland and pasture development and improvement involves selection of sites, protection from biotic factors, grubbing out unwanted bushes, propagation of top feed cum shade trees, adoption of soil conservation measures, stabilization of sand dunes, forage production, reseeding with appropriate grass species, fertilization, development of water resources, rodent control and controlled animal husbandry to help establish productive range for their long term utilisation in profitable livestock production. The available information on all these aspects, based on data obtained in the Rajasthan desert, has been presented in this paper.